Characterization of the Material Produce by Wire Arc Additive Manufacturing GTAW Material AISI 308L - Sarwono, Edi; Ardiyansyah, Dito (Jurnal Rekayasa Mesin, 2026)
This study examines the microstructural evolution and mechanical performance of AISI 308L stainless steel produced by Wire Arc Additive Manufacturing (WAAM) using the Gas Tungsten Arc Welding (GTAW) process. Specimens were sectioned into bottom, middle, and top regions to assess the effects of thermal cycling on hardness and tensile properties. Distinct microstructural and mechanical variations were observed along the manufacturing height. The bottom region, subjected to repeated reheating, exhibits coarse columnar and dendritic grains with a high δ-ferrite content, resulting in the lowest tensile strength (540 MPa) and hardness (230-255 HV), but the highest ductility (45% elongation). The middle region, influenced by in-situ thermal treatment, develops finer equiaxed grains and reduces porosity, resulting in increased tensile strength (547 MPa) and hardness (230-255 HV) with moderate ductility (35-38%). The top region, characterized by rapid cooling, forms fine equiaxed grains with minimal δ-ferrite, resulting in the highest hardness (265 HV) and tensile strength (546 MPa), albeit with reduced ductility (28-30%). These results extend previous investigations by quantitatively explaining the trade-off between strength and toughness across the WAAM layer. These findings confirm that grain refinement increases hardness and strength through grain boundary strengthening, while coarser grains increase ductility. Overall, this study underscores the important role of thermal history in tailoring mechanical performance and challenges the oversimplified notion that finer grains are always advantageous.